2014
DOI: 10.18632/oncotarget.1909
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neoplastic properties of hydralazine in prostate cancer

Abstract: Prostate cancer (PCa) is a major cause of cancer-related morbidity and mortality worldwide. Although early disease is often efficiently managed therapeutically, available options for advanced disease are mostly ineffective. Aberrant DNA methylation associated with gene-silencing of cancer-related genes is a common feature of PCa. Therefore, DNA methylation inhibitors might constitute an attractive alternative therapy. Herein, we evaluated the anti-cancer properties of hydralazine, a non-nucleoside DNA methyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 40 publications
(48 reference statements)
4
45
0
Order By: Relevance
“…The transcription factors E26 transformation-specific sequence-1 and -2, implicated in controlling miR-126 expression, were unchanged 24 in CRVH compared with DRV ( Figure IIIC in the online-only Data Supplement). Although the beneficial effects of hydralazine as a vasodilator are attributed to K + channel opening in ECs, 41 other potential effects include DNMT inhibition 30 and thus DNA methylation, which is known to regulate miR-126 expression. 42 Even if the effects of hydralazine on DNA Figure IIID-IIIG in the online-only Data Supplement).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factors E26 transformation-specific sequence-1 and -2, implicated in controlling miR-126 expression, were unchanged 24 in CRVH compared with DRV ( Figure IIIC in the online-only Data Supplement). Although the beneficial effects of hydralazine as a vasodilator are attributed to K + channel opening in ECs, 41 other potential effects include DNMT inhibition 30 and thus DNA methylation, which is known to regulate miR-126 expression. 42 Even if the effects of hydralazine on DNA Figure IIID-IIIG in the online-only Data Supplement).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, methylation has been implicated in PAH pathogenesis 28 with the upregulation of DNA methyl transferase (DNMT). 29 Thus, DRV ECs were treated with hydralazine (a DNMT inhibitor 30 ). Hydralazine dose-dependently increased miR-126 in DRV ECs ( Figure IIID in the online-only Data Supplement).…”
Section: Overexpression Of Mir-126 In Vitro Restores the Angiogenic Pmentioning
confidence: 99%
“…[8, 37, 38, 44, 45] DNMTIs were shown to cause replication lesions through which double-strand breaks of DNA, radial chromosomes and chromatid breaks are induced. [44] Jiemjit et al found that DNA damage also occurred in DNMT−/− cells exposed to DNMTIs, indicating that such effect is DNMT inhibition-independent.…”
Section: Discussionmentioning
confidence: 99%
“…Genetically modified PC-3 VIRMA CRISPR knockdown (PC-3 KD ) was generated by Synthego Corporation with the following guide RNA sequence: 5 CUAUGGGCUCUUACUCCUGG 3 . Cell culture were performed accordingly [55].…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%